The Red Rock ice cliff revisited – six decades of frontal, mass and area changes in the Nunatarssuaq area, Northwest Greenland - Jakob Abermann; Jakob F Steiner; Rainer Prinz; Matthias Wecht; Peter Lisager (Journal of Glaciology, 2020)
We present changes of the ice margin in Northwest Greenland at the Eastern part of the Nunatarssuaq Ice Cap (NIC) over six decades. The ice margin in this area terminates as a near-vertical ice cliff of between 9 and 33 m thickness. During the years 1954–1957 and in 1965 multi-disciplinary studies were performed. We digitise and orthorectify material, that is often difficult to access, in order to use the historical data as an absolute starting point of our change assessment. We compare the cliff morphology of the mid-1950s and the mid-1960s with various time-steps between 1985 and 2017. The studied ice margin remained remarkably constant with very subtle changes of changing sign: rather slow advance rates are reported from the 1950s and 1960s that accelerated until 1985 and were followed by a general retreat until 2012 and a subsequent advance until 2017. Thickness changes are negative throughout the entire time-period, however, different rates of thinning are shown and there is a positive relationship with air temperature anomalies. Compared to similar elevations on the adjacent Greenland ice sheet, we find significantly weaker thinning rates at the NIC.